Subcultura tuning: a identidade estendida na personalidade de automóveis - Silva, Rogério Ramalho da (2007)
The admiration of people for automobiles has been known and revealed for many years all over the world. Being through academic studies, proprietor declaration and admirers, the automobile is an object of desire, admiration, love, passion, dream, pride and accomplishment which, with all of this, promotes various types of feelings with the identification, discrimination, expression and the projection of identity. This research was based on the theories about consumers¿ behaviors, self-concept and extended self. It'll be approached in a qualitative and exploratory way the personal behavior of the consumers who personalizes their automobile, the consumer Tuning. The Objective of this project is to explore how the ¿Tuners¿ use a personalized car to construct their social identity. Supplementary, was explored which factors commence and initiated the extension process of self-automobile and also, how they connect with their object and why this relationship is establish this way. Seven people were interviewed of the male sex between 19 and 33 years old, living in the stated of Rio de Janeiro and São Paulo, during the period of September and October of the year 2007. The results observed were that the cars, like objects, can literally broaden its owner¿s personality. The creation process, sustentation and nutrition of the ¿Self¿ through the car can be observed in the personalization of their own cars, with this, using like the middle and end. It was also observed that the begin of the personalization phenomenon of automobiles in Brazil is began, mainly, in the 21 century with the diffuser of the culture, the cinema, evince even more, processes that already existent in the extension of the personalized cars. Observing that a personalized automobile tents to be in a free way, like a distance, when possible, from intransigence of models or imposition of the ways to be accomplished. Definitively, stories like: ¿My car is just a useful way to travel which I use only when necessary¿ will not be found in this research.